Basic care as exceptional care: addiction stigma and consumer accounts of quality healthcare in Australia. Issue 2 (4th May 2021) - Farrugia, Adrian; Pienaar, Kiran; Fraser, Suzanne; Edwards, Michael; Madden, Annie
ABSTRACT: The discrimination faced by people understood to have alcohol or other drug addictions has been the subject of extensive research, with many studies documenting experiences of stigma within healthcare services. Building on this literature, we examine the role of stigma in shaping the healthcare expectations of people seen as affected by alcohol and other drug addictions. Our analysis draws on recent theorisations of stigma as a process of social production to analyse in-depth, qualitative interviews with 20 people who had recently attended an inpatient withdrawal management service. Participants describe as exceptional forms of care that are often taken for granted by other members of the community. We argue that routinised experiences of discrimination work to constitute basic care as exceptional. This finding is significant for two reasons: (1) people who consume alcohol and other drugs often have complex healthcare needs and already encounter obstacles to accessing the care they need, and (2) by positioning people who consume drugs outside the purview of healthcare, this dynamic obstructs their fundamental right to care. We conclude by reflecting on the implications of these findings for those who are often positioned as not entitled to high quality healthcare.